PENERAPAN MODEL PEMBELAJARAN BERBASIS PORTOFOLIO DALAM MENINGKATKAN HASIL BELAJAR PKN - Hendra Saputra S Adiko; Riska Maksud (Jurnal Ilmu Pendidikan UMGo, 2024)
The problem in this study is "Improving Student Learning Outcomes in the material of ethnic and religious diversity in my country. Class IV Pkn Subjects through a Portfolio-Based Learning Model at SDN 4 Bone, Bone Bolango Regency?" The purpose of this study was to improve student learning outcomes in the material of ethnic and religious diversity in my country. Class IV Pkn Subjects through a Portfolio-Based Learning Model at SDN 4 Bone, Bone Bolango Regency. The method used in this research is Classroom Action Research (CAR) which is carried out in 2 cycles. Data collection techniques in this study were in the form of teacher activity observation, student activity observation, interviews, tests, and documentation. Initial observations of students' learning outcomes the average student in the material of ethnic and religious diversity in my country (29%) or 5 students who have completed and (71%) or 12 students who have not completed. In the implementation of the first cycle class action, only 12 students (71%). In the second cycle it increased to 15 people (88%). From the results of the research and discussion conducted, the study of student learning outcomes on the material of ethnic and religious diversity in my country using the Class IV Portfolio-Based Learning Model of SDN 4 Bone, Bone Bolango Regency increased.